Experimental transmission of Caryospora bigenetica Wacha et Christiansen, 1982 (Apicomplexa: Eimeriidae) from a rattlesnake, Crotalus atrox, to rodents and pigs - Koudela, B.
Caryosporan oocysts were found in the feces of a diamond rattlesnake, Crotalus atrox, kept in ZOO Ústí nad Labem, Czech Republic. Comparison of oocyst structure with hitherto described Caryospora species from snakes revealed that they were Caryospora bigenetica Wacha et Christiansen, 1982. The rattlesnake, Crotalus atrox, represents a new host for C. bigenetica. The common vole (Microtus arvalis) and gerbil (Meriones unguiculatus) were successfully infected with a mixture of C. bigenetica oocysts and sporocysts following oral inoculation. All experimentally infected animals displayed clinical signs of dermal coccidiosis, including swellings of the face, ears, footpads, and scrota or vagina. Gerbils developed more severe clinical signs of infection and had a higher mortality than voles. Developmental stages of C. bigenetica were found in connective tissue of the nose, cheeks, ears, scrotum or vagina. Transmission of C. bigenetica caryocysts between common voles and mice, between mice and common voles, common voles and gerbils, and common voles and pigs was demonstrated. This study demonstrates that C. bigenetica can be transmitted by predation or cannibalism between different species ofrodents and pigs.